Soil properties and earthworm dynamics affected by land use systems in western Chitwan, Nepal - Chauhan, R. P.; Pande, K. R.; Shah, S. C.; Dhakal, D. D. (Journal of the Institute of Agriculture and Animal Science, 2018)
Field experiments were conducted in acidic soils of Mangalpur and Fulbari Village Development Committees in western Chitwan, Nepal to study the effects of different land use systems on soil properties and earthworm dynamics. Seven land use systems (cereal based lowland, cereal based upland, vegetable farm land, fruit orchard land, pasture land, forest land and farmer’s field) were used and they were replicated four times in randomized complete block designs. Soil organic matter and total soil nitrogen were significantly higher from pasture land (4.7 % and 0.2 %) and the lowest were from farmer’s field (2.4 % and 0.1 %). However, available soil phosphorous content was significantly higher from cereal based upland (448.3 kg ha-1) and it was the lowest from forest land (13.0 kg ha-1). The highest earthworm count was observed from pasture land (10.1 numbers per trap) than others but it was the lowest from farmer’s field. There were significant positive correlations between soil organic matter content and the earthworm count (r= 0.96**) and between total soil nitrogen content and earthworm count (r= 0.80**). In contrast, a significant negative correlation was observed between earthworm count and available P (r= -0.51**). Correlation between earthworm count and silt content was positive (r= 0.68**) but between earthworm count and sand content was negative (r= -0.64**). However, there were no significant relationships of earthworm count with available K, pH, bulk density and clay content of soils. The soil organic matter, total soil nitrogen and earthworm count were higher from pasture soil than other soils. As soil organic matter, total soil N, available soil P and soil texture regulated earthworm dynamics in soils. Earthworm population may be used as a bio-indicator of soil fertility status and it can be developed as an alternative technique for soil fertility evaluation after quantification and verification from further experiments on earthworm dynamics under different land use systems. Journal of the Institute of Agriculture and Animal Science. Vol. 33-34, 2015, page: 123-128